2012
DOI: 10.2217/fmb.12.17
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress Resistance in Porphyromonas Gingivalis

Abstract: Porphyromonas gingivalis, a black-pigmented, Gram-negative anaerobe, is an important etiologic agent of periodontal disease. The harsh inflammatory condition of the periodontal pocket implies that this organism has properties that will facilitate its ability to respond and adapt to oxidative stress. Because the stress response in the pathogen is a major determinant of its virulence, a comprehensive understanding of its oxidative stress resistance strategy is vital. We discuss multiple mechanisms and systems th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(74 citation statements)
references
References 97 publications
(156 reference statements)
1
72
0
1
Order By: Relevance
“…Because the stress response in the pathogen is a major determinant of its virulence, a comprehensive understanding of its oxidative stress resistance strategy is vital [6]. …”
Section: Porphyromonas Gingivalismentioning
confidence: 99%
“…Because the stress response in the pathogen is a major determinant of its virulence, a comprehensive understanding of its oxidative stress resistance strategy is vital [6]. …”
Section: Porphyromonas Gingivalismentioning
confidence: 99%
“…In addition, during periods of mechanical disruption of dental plaque, anaerobes associated with periodontal disease may be exposed to oxygen. Although periodontal disease-associated anaerobes lack or express low levels of superoxide dismutase and catalase to detoxify ROS compared to aerobes or facultative anaerobes (24)(25)(26), production of H 2 S can serve as a means to reduce the overall oxygen tension in the local environment to enhance survival during periods of oxidative stress. Indeed, in this study, we showed that the reducing property of H 2 S sustained the viability of F. nucleatum under aerobic conditions for a prolonged duration.…”
Section: Fig 3 Effects Of H 2 S On Intracellular Sulfide Levels and Gmentioning
confidence: 99%
“…Earlier reports have documented an inducible protective system in response to oxidative stress (3,6). A transcriptome examination revealed that P. gingivalis is able to prioritize the response by first protecting and repairing its genetic material and then subsequently repairing any damaged proteins (6).…”
Section: Discussionmentioning
confidence: 99%